Effectiveness of printed nutrition education media on dietary knowledge, dietary adherence, and glycemic control among patients with type 2 diabetes mellitus: A narrative literature review - Wahyu Ria Wijayanti; Intan Yusuf Habibie (AcTion: Aceh Nutrition Journal, 2026)
Type 2 diabetes mellitus is a chronic metabolic disorder with increasing prevalence, necessitating appropriate dietary management to prevent complications. Evidence indicates that most patients exhibit low dietary adherence, which directly affects glycemic control, and limited dietary knowledge remains a primary barrier. Print-based nutrition education, including leaflets, booklets, and pocket guides, is widely employed because of its practicality, affordability, and capacity for repeated consultation. This narrative literature review examines the effectiveness of print-based nutrition education in enhancing dietary knowledge, adherence, and glycemic outcomes in patients with type 2 diabetes. Literature searches were conducted in Google Scholar, Taylor & Francis, and Dimensions using relevant keywords, and selections were made following the PRISMA framework. Of the 510 identified articles, three met the inclusion criteria. The findings consistently demonstrate that print-based nutrition education improves dietary knowledge among patients. Pocket guides were generally more effective than leaflets, offering convenient and repeatable use. Improvements in dietary adherence and blood glucose levels were more pronounced when printed materials were supplemented with repeated counseling and dietary monitoring. In conclusion, print-based nutrition education effectively enhances dietary knowledge and is a viable tool for diabetes care.